Hydrological Modeling of the Tampaon River in the Context of Climate Change - Velázquez, Juan Alberto; Troin, Magali; Caya, Daniel (Tecnología y ciencias del agua, 2015)
This work compares the hydrological modeling of the Tampaon River Basin (in east-central Mexico) with two hydrological models (SWAT and GR4J) and then evaluates the impact of climate change on the water balance of the basin. The calibration and validation of the models (over 14-year periods) show that both performed satisfactorily when simulating daily flows. The results indicate that SWAT more precisely reproduces observed mean monthly streamflow while GR4J overestimates it during the dry season and underestimates it during the rainy season. The analysis of the impact of climate change was performed by using climate ensemble simulations derived from the Canadian Global Climate Model (CGCM3) downscaled by the Canadian Regional Climate Model (CRCM). The climate simulations (after bias correction) were used as input data for both hydrological models for two periods: a reference period (1971 – 2000) and a future period (2041-2070). The results indicate a significant decrease in mean monthly streamflow in the Tampaon River Basin for the future period (-36 to -55%), as well as a decrease in maximum monthly streamflow (-34 to -60%) and minimum monthly streamflow (-36 to -49%). The results from this study provide an overall perspective of the potential impact of climate change on the hydrological response of the Tampaon River Basin.